Effectiveness of Planned Teaching Programme (PTP) On Knowledge Regarding “FAST HUGS BID” Mnemonic among B.Sc. Nursing Final Year Students - Miss. Monika Bhonde; Mr. Amos Talsandekar, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background and objectives: A critical care unit is a constantly overcrowded ward where terminally ill patients get life-sustaining treatment while being closely monitored. Innovative therapeutic approaches are frequently implemented in ICUs to enhance patient care so FASTHUGSBID mnemonic used in Intensive care unit for proper management of patient care by the health care personnels. The FAST HUG mnemonic was created by Sir JL Vincent. He wrote an article named “Give your patient a FAST HUG (at least) once a day” in the year 2005. Later it was modified by WR Vincent and Hatton and made FAST HUGS BID1. The FAST HUGS BID, has been established to promote communication among nursing and physician caregivers in the ICU5. Critical care nursing demands a structured and evidence-based approach to ensure comprehensive patient management. The mnemonic FAST HUGS BID (feeding, analgesia, sedation, thromboembolic prophylaxis, head-of-bed elevation, ulcer prophylaxis, glycemic control, spontaneous breathing trial, bowel regimen, indwelling catheter removal, de-escalation of antibiotics) serves as valuable checklist for optimizing intensive care unit (ICU) patient care. It helps health care providers systematically assess and address key aspects of critical care, reducing complications and improving patient outcome. Hence, there is need to provide knowledge on FASTHUGSBID among B.Sc. Nursing Final Year students studying in D.Y. Patil College of Nursing, Kolhapur. Objectives of the study were, To Assess the Pre-Test Knowledge scores regarding “FAST HUGS BID” mnemonic among B. Sc. Nursing Final year students, To evaluate the effectiveness of Planned teaching Programme on “FAST HUGS BID” mnemonic among B. Sc Nursing Final year students, To find out an association between mean pre-test knowledge score on “FAST HUGS BID” mnemonic and selected sociodemographic variables of B.Sc. Nursing final year students. Methods: The research approach adopted for the study was quantitative evaluative and design was quasi-experimental, one group pre-test post-test design. By using simple random sampling technique 80 students were selected from B.Sc. Nursing final year at D. Y. Patil College of Nursing, Kolhapur. Structured knowledge questionnaires were used to assess the knowledge regarding FAST HUGS BID mnemonic. The reliability of the tool was tested by using test-retest method and Spearman`s Brown formula. The reliability computed was r = 0.80. Data were analysed by using mean, median, mode, range, standard deviation, paired‘t’ test, chi square test. Result: In the pretest, majority of 43(56.3%) participants had average knowledge,25 (31.3%) participants had poor knowledge and 10(12.5%) participant had good knowledge. In the post-test, majority of 45(56.3%) participants had good knowledge and 30(37.5%) participants had average knowledge and 5(6.3%) had poor knowledge score regarding FAST HUGS BID mnemonic. The p value (0.001) is less than 0.05 level of significance and (ttab value -24.32). The findings reveals that the planned teaching programme (PTP) is effective in improving knowledge score among students. There is significant association between knowledge score and gender. (p value = 0.008). There is significant association between knowledge score regarding FAST HUGS BID mnemonic and selected sociodemographic variables among B.Sc. Nursing final year students studying in selected college of nursing at 0.05 level of significance. Interpretation and conclusion: The overall findings showed that in pretest the majority of students had average knowledge score and in post-test the majority of students had good knowledge score. There was significant association between knowledge score regarding FAST HUGS BID and gender. So it conclude that the planned teaching programme (PTP) was effective in improving the knowledge regarding FASTHUGSBID mnemonic among B. Sc Nursing Final year students.